2017
DOI: 10.4103/0366-6999.198916
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Psychiatric Disorders in Women with Polycystic Ovary Syndrome in Southwest China

Abstract: Background:Polycystic ovary syndrome (PCOS) and its characteristic symptoms have been associated with physical and psychological issues in women of reproductive age. The current study was conducted in response to the dearth of systematic research related to psychological functioning and quality of life in patients with PCOS in Southwest China, and to determine whether patients with PCOS exhibit poorer mental health (MH) compared to healthy women of the same age and living in the same region, without a PCOS dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 18 publications
0
43
0
2
Order By: Relevance
“…Similar studies showed that the prevalence of depression and anxiety were higher among PCOS cases than controls. 14 , 35 The most prevalent psychological burden reported in literature was anxiety. In the systematic review reported by Dokras et al, 36 the rate of generalized anxiety symptoms was noted to be higher in PCOS women than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies showed that the prevalence of depression and anxiety were higher among PCOS cases than controls. 14 , 35 The most prevalent psychological burden reported in literature was anxiety. In the systematic review reported by Dokras et al, 36 the rate of generalized anxiety symptoms was noted to be higher in PCOS women than controls.…”
Section: Discussionmentioning
confidence: 99%
“…A prevalência de desordens mentais em indivíduos com Síndrome do Ovário Policístico é bastante alta comparando-se aos grupos controle, e isso indica um risco aumentado do desenvolvimento dessas doenças nas portadoras de SOP. Ao utilizar instrumentos como o Escore de Depressão de Beck, evidenciou-se que grande parcela das mulheres com SOP possuem depressão severa, indicando essa forte correlação (TAN, et al 2017). está revisão mostra que mostra que as mulheres com SOP estão em um risco significativo de transtornos depressivos, fobia social e transtornos de ansiedade, além do mais, distúrbios bipolares recentemente diagnosticados, tem sido frequentemente relatado na literatura como risco comórbido com SOP, apesar de não ser elevado.…”
Section: Resultsunclassified
“…Kercher et al showed that the overall prevalence of depression was 40% in women with PCOS (21). In a recent study, Tan et al found the frequency of depression as 27.5% in PCOS, which was higher than HCs (22). Anxiety disorders and depression were the most common psychiatric disorders in PCOS in Turkey (23, 24).…”
Section: Discussionmentioning
confidence: 99%